Anti-Inflammatory Effects of Cerium Dioxide Nanoparticles on Peritonitis in Rats Induced by Staphylococcus epidermidis Infection - Yan Li; Hongmei Sun; Zhiqi Yin; Xuexi Guo; Jun Yan (Advances in Polymer Technology)
Objective. To investigate the effects of cerium dioxide (CeO2) nanoparticles on the inflammatory response of peritonitis rats induced by Staphylococcus epidermidis infection. Methods. Green tea polyphenol CeO2 nanoparticles were synthesized and characterized by transmission microscopy, ultraviolet-visible spectroscopy, FT-IR, and powder diffractometer. 40 male adult SD rats were randomly divided into 4 groups (n = 10 each): a control group, a model group, a CeO2 group, and a CeO2 + model group. Staphylococcus epidermidis solution was injected intraperitoneally with 107 CFU/ml of bacterial solution in the model group, while the control group was injected intraperitoneally with the same amount of normal saline, and the CeO2 and CeO2 + model groups were injected with 0.5 mg/kg CeO2 nanoparticles through the tail vein for 2 h and then injected with saline or bacterial solution for 2 h, respectively. After 0 h, 3 h, 12 h, 24 h, and 48 h of model construction, rats were sacrificed, and serum and peritoneal lavage fluid were collected. The total number of leukocytes and the percentage of each type of leukocytes in the peritoneal lavage fluid were determined. Enzyme-linked immunosorbent assay (ELISA) was used to detect the level of inflammatory factor TNF-α in serum and peritoneal lavage fluid, and myeloperoxidase (MPO) activity in peritoneal tissue was also measured. In addition, real-time fluorescence quantitative PCR (RT-PCR) was used to measure the expression of TLR2 and TLR4 in peritoneal tissue, and western blotting was used to detect the expression of TLR2, TLR4, and the activation of NF-κB signaling pathways as well. Results. The CeO2 has an average size of 37 ± 3 nm with binding activity to proteins, phenolic compounds, and alkaloids. After counting the white blood cells in the peritoneal lavage fluid, it was found that the total number of white blood cells and the percentage of neutrophils in the model group were significantly increased (both P<0.05), and CeO2 treatment significantly reversed the above changes (both P<0.05). The ELISA results showed that compared with the control group, the TNF-α in the peritoneal lavage fluid and serum of the model group increased in a time-dependent manner (all P<0.05); however, there was no significant change in the CeO2 group (P>0.05); at the same time in the CeO2 + model group, the TNF-α content was significantly reduced (all P<0.05). Detection of MPO activity in peritoneal tissue revealed that MPO activity was significantly increased under peritonitis (all P<0.05), and CeO2 treatment could mitigate that increase (all P<0.05). RT-PCR results showed that compared with the control group, the expression of TLR2 and TLR4 mRNA levels in the peritoneum of the model group were increased in a time-dependent manner (all P<0.05), and there was no significant change in the CeO2 group (P>0.05); however, TLR2 and TLR4 mRNA levels were significantly reduced in the CeO2 + model group (all P<0.05). Western blotting test was performed on the peritoneal tissue collected after 48 h of the model establishment. Compared with the control group, the levels of TLR2, TLR4, p–NF–κB, and p-IκBα protein in the model group were significantly increased (all P<0.05), while CeO2 group showed no significant changes (P>0.05) and administration of CeO2 before model construction can significantly reverse the above protein activation (all P<0.05). Conclusion. CeO2 nanoparticles have anti-inflammatory effects in peritonitis caused by Staphylococcus epidermidis infection.